Representations of the Romanian Holocaust in testimonial literature and films: from trivialization, denial to working through the past (part 1) - Arleen Ionescu; Dumitru Tucan (Swedish Journal of Romanian Studies)
Synthesizing the way in which the Romanian Holocaust has been represented in testimonial literature and films, this article deals with notions such as Holocaust trivialization and denial, as well as with “mastering the Romanian past” of the interwar period and WW2. The article is a cartography of the representations of the Romanian Holocaust; to that end, it follows the chronology of post-1945 published literary works (documentary texts, memoirs and fiction) and documentary and artistic films which were produced about the Romanian Holocaust in Romania and outside Romania.